Establishment and maintenance of the DNA methylation pattern in the human alpha-globin cluster - Gaentzsch, R (2013)
DNA methylation is an epigenetic modification that plays an important role in development and differentiation. The patterns of DNA methylation are largely established in early embryogenesis and maintained during development. Abnormal DNA methylation patterns have been associated with many human diseases, including cancer. Despite its importance, little is currently known about the mechanisms that determine DNA methylation patterns throughout the genome. To shed light on the molecular mechanisms that regulate DNA methylation, this study investigates whether DNA methylation patterns are established and maintained normally when human DNA is placed into a heterologous murine environment as opposed to its natural, endogenous chromosomal environment. Here, a previously generated transgenic mouse model, containing 117 kb of human DNA bearing the human α-globin cluster and all of its known regulatory elements, was analysed. The pattern of DNA methylation of the endogenous human α-globin cluster was compared with that of the transgenic cluster in the background of mouse embryonic stem cells (ESCs) and tissues. It was found that, although the normal human DNA methylation pattern was largely established and maintained in a mouse background, the region immediately around the human α-globin genes themselves is generally less methylated in mouse compared to human ESCs. It was found that regions adjacent and up to 2kb from the CpG islands (CGIs), so-called CGI shores, were unusually hypomethylated: this seems to be the result of an extension of CGIs in humanised mouse (hm) ESCs compared to human (h) ESCs. Furthermore, this hypomethylation appeared to increase during development in both erythroid and non-erythoid cells. To identify any cis-regulatory sequences responsible for the hypomethylated state of human CGI shores in the mouse, 2-4 kb human test sequences containing the CGI associated with the human α-globin 2 (α2) gene and its adjacent hypomethylated shore were re-integrated into the mouse α-globin locus via recombination-mediated cassette exchange (RMCE). Human CGI shores became hypomethylated in the context of the re-integrated test sequences, indicating that the appearance of hypomethylation is determined by the underlying human DNA sequence in the test fragments. In summary, the data presented here reveal that human CGIs become extended when placed in a mouse background leading to hypomethylation of human CGI shores in the mouse compared to the pattern of methylation at the normal endogenous human locus. These findings suggest that species-specific factors determine DNA methylation near CGIs. The transgenic mouse model provides an excellent system to dissect out species-specific regulation of CGI shore methylation. Furthermore, this study lays the foundation for future experiments addressing the role of DNA methylation in regulating human gene expression in the murine context, and examining the validity of transgenic mouse models for the study of human gene regulation.